Analisis Tingkat Pengetahuan dalam Pemanfaatan Layanan Mobile JKN - Nurhidayah, Nurhidayah; Purba, Quen Kholisa; Sitorus, Rehana Nugraha B.; Gurning, Fitriani Pramita (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The mobile JKN application is the latest innovation from BPJS health in improving services to the public, especially in the health sector, which can be accessed through smartphones. However, many people still do not utilize this application. This study aims to determine the utilization of the mobile JKN application and measure its effectiveness in improving public health services. The method of writing this journal involves searching for articles through Google Scholar and PubMed with the keywords "utilization of mobile JKN services". This application allows membership registration and provides health services such as health counseling, immunization, family planning, and health screening effectively. Thus, it is expected that through this digitalization, at least 98% of the population in Indonesia can become mobile JKN participants, ensuring equal quality of health services. Research results from experts also show that the use of mobile JKN has satisfactory quality for its users, although many people are still unaware of the existence of this application.